PENGUJIAN KELAYAKAN ALAT PELINDUNG DIRI ( LEAD APRON DAN THYROID SHIELD) - Thalia Devi Prama Dani; Darmini (JRI (Jurnal Radiografer Indonesia), 2018)
Radiation Protection Tool in Radiology Departement Of RS PKU Muhammadiyah Yogyakarta there are four Lead Apron and Thyroid Shield. Maintance of Lead Apron and Thyroid Shield has not done well and has not been done by X-ray testing. This study aims to determine maintance of Lead Apron and Thyroid Shield, determine the results of Lead Apron and Thyroid Shield, to determine Lead Apron and Thyroid Shield tests are still feasible to use or not. The kind of research that used is descriptive quantitative research with survey approach. Data collection is done by direct observation, testing, measurement and documentation. The observations were conducted directly an four Lead Apron and Thyroid Shield in Radiology Departement Of RS PKU Muhammadiyah Yogyakarta. The testing was done with radiating all Lead Apron and Thyroid Shield and recorded with Computed Radiography. The data obtained are then analyzed. Appropriatness Lead Apron and Thyroid Shield are not feasible to use if the damage in the form a hole of 2 mm or area exceeds 3,14 mm2 and damage in the form of fault with a lenght exceeding 4 mm. The results of this research indicate that the maintance of Lead Apron and Thyroid Shield is not done well and correctly. Lead Apron and Thyroid Shield placed hung up, folded and placed not on a special cabinet. According the result Lead Apron and Thyroid Shield can be recognized that there is one Lead Apron is not feasible because it has hole damage in the form of 2 mm or area exceeds 3,14 mm2 and damage in the form of fault with a lenght exceeding 4 mm. But for Lead Apron A, B, D and Thyroid Shield although there are indentation and fractures but not exceeding the specified standart so it is still feasible to use.